Dossier I: Mecanismos psicológicos de defensa que operan en la obtención del testimonio - Pérez-Campos Mayoral, Eduardo (Quadernos de criminología, 2021)
Psychology has brought discoveries to the legal world about the psychological processes involved in communication. Research on personality have found evidence of defense mechanisms that operate in communication processes. Understanding these processes makes it easier to obtain information in an investigative interview through specific techniques, avoiding the activation of psychological defenses that decrease the amount of information obtained. This work analyzes how these defense mechanisms operate when a testimony is obtained.